(untitled) (Archives of Clinical and Medical Case Reports, 2021)
Although cardiac magnetic resonance (CMR) may proof useful in the diagnosis of myocardial injury triggered by COVID-19, limited experience has yet been published. We report several cases presenting its utility at various COVID-19 disease stages in diagnosing different cardiac manifestations. The current COVID-19 crisis will undoubtedly transform CMR imaging Units.